2006
DOI: 10.1159/000091898
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Dysfunction Related to Both Apathy and Disinhibition in Frontotemporal Dementia

Abstract: Orbitofrontal metabolic impairment is characteristic of the frontal variant of frontotemporal dementia (fv-FTD), as are early changes in emotional and social conduct. Two main types of behavioral disturbances have been distinguished in fv-FTD patients: apathetic and disinhibited manifestations. In this study, we searched for relationships between brain metabolism and presence of apathetic or disinhibited behavior. Metabolic activity and behavioral data were collected in 41 fv-FTD patients from European PET cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(132 citation statements)
references
References 61 publications
10
116
1
5
Order By: Relevance
“…reported that orbitofrontal dysfunction is related to both apathy and disinhibition in FTD patients (Peters et al, 2006). In accordance with this we noted increased tau immuno-reactivity and NFT formation by silver staining in 12 month-old Tg animals.…”
Section: Discussionsupporting
confidence: 91%
“…reported that orbitofrontal dysfunction is related to both apathy and disinhibition in FTD patients (Peters et al, 2006). In accordance with this we noted increased tau immuno-reactivity and NFT formation by silver staining in 12 month-old Tg animals.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Marshall and colleagues, employing PeT in Ad patients with mild to moderate dementia, showed that apathy was related to hypometabolism in ventromedial PFc, including the ventral Acc and medial oFc 61 , as predicted and described below in our proposed account for neurobiology of apathy in Ad. PeT data from frontal variant of frontotemporal dementia (fvFTd) has also shown a significant relationship between apathy and oFc hypometabolism 62 . It should be stressed that given decision-making is a dynamic process, resting PeT or sPecT may lack the optimal spatio-temporal resolution to infer the underlying behavioral neurophysiology 63 , and may have higher sensitivity in more advanced stages of dementia.…”
Section: Apathy Alzheimer's Disease and Other Cortical Dementias: Nementioning
confidence: 99%
“…Converging evidence now suggests that the self-perspective is the cognitive "default mode," and therefore, to evaluate another's perspective, some form of active inhibitory mechanism must regulate the prepotent self-perspective. However, although loss of empathy is a common feature of neurodegenerative disease, the only studies that have assessed the relationship between cognitive inhibition and empathy in relation to dementia have focused on frontotemporal dementia (Lough et al, 2006;Peters et al, 2006), and thus the relationship between cognitive disinhibition and empathy in individuals with AD remains to be established. ular importance has been attributed to the processes of reappraisal and suppression.…”
Section: Cognitive Inhibition and Empathymentioning
confidence: 99%